IMPLEMENTATION OF SHARIA PRINCIPLE (PROFIT SHARING AND RISK) IN BUSINESS ACTIVITY OF KOPPONTREN ASSALAAM - Mujiburohman - - (Pondok Pesantren Modern Islam Assalaam, 2017)
Shari’a Islamic economic developments in Indonesia, which has the largest Muslim population,are welcome by financial service businesses by setting up Shari’a banks, baitul mal wattanwil and others. As the pillar of the Indonesian economy, cooperatives which play important roles in economic development in Indonesia do not overlook capturing the opportunities in the field of savings and loans based on Shari’a. The problems that is faced are the implementation of the principle of profit sharings and risks involved in fund raising activities, the implementation of the principle of profit sharings in financing activities in a cooperative and the operational obstacles encountered in the implementation of the principle of the results of those profit sharings. This study not only uses qualitative research methods with empirical juridical approach, naturally observes at the basic principles of Islamic shari’a financial as a normative in nature, but also see how to interact (to be implemented) in the community. One of the principles of Shari’a financial is a contract for the result of profit sharings and risks in which the cooperative and also the members share the profits based on the ratio of the profit sharings that is determined before. The principle of profit sharings is the main characteristic in Islamic Shari’a finance, but financing activities in the cooperative are still low in comparison with other financing activities such as Murabaha (sale and purchase), this is affected by partially because of the high risks that must be paid by the cooperative in case of loss as a result of non intentional action or negligence of the debtors so that the cooperative will be very cautious in providing financing to members. Other constraints are inadequate human resources, management, information systems and technology, the attitude of the members of the cooperative who are more familiar with the conventional patterns and the lack of moral standards which are applied in financing activities.